Kebutuhan Metode Kontrasepsi Jangka Panjang Pada Akseptor KB Suntik Berdasarkan Penggunaan Kontrasepsi Rasional di Puskesmas Wirang - Fathiyah, Fathiyah; Lathifah, Nur; Hateriah, St (Jurnal Rumpun Ilmu Kesehatan, 2024)
One of the strategies for the Family Planning (KB) program to reduce maternal and infant mortality is to minimize the 4T conditions. Contraceptive use is still dominated by short-term contraceptive methods, especially injections and pills. Only a quarter of family planning participants use long-term methods of contraception, such as IUDs and implants. The Research objective is to analyze the need for long-term contraceptive methods for injection acceptors based on rational contraceptive use at the Wirang Public Health Center. The method is types of descriptive research. Time of study January 2023. The sample is 168 people. The data source for this research was secondary data in October 2022 regarding injecting birth control acceptors which were analyzed univariately. This study obtained the results of MKJP contraceptive needs based on the phase of contraceptive use (rational contraception), is in the phase of ending the pregnancy as many as 93 people (55.36%). Concluded that contraceptives used by WUS injecting family planning acceptors are not in accordance with rational use of contraception. With age > 35 years or having > 2 children and the pregnancy termination phase, the contraceptive method needed is MKJP contraception.